Kinematic asymmetries of the lower limbs during ergometer rowing - Buckeridge, E.; Bull, A. M.; McGregor, A. H. (The biomedical basis of elite performance. 19-21 March 2012, London, UK. Abstracts & Manuscripts, 2012)
Rowing injuries, particularly of the lumbar spine, are often attributed to poor technique. Rowing technique comprises a series of coordinated movements between the back, upper limbs and lower limbs, and abnormalities in these may lead to injury (Bull & McGregor, 2000). The primary aim of this study was to test the hypothesis that ergometer rowing is symmetrical with respect to lower limb motion, and that deviations from symmetry result from rowing experience, work rate, or stroke position. A secondary aim was to examine the relationship between lower limb asymmetries and lumbar-pelvic kinematics. Twenty-two rowers in three levels of ability (8 elite, 8 club, 6 novice) participated in an indoor rowing step-test at four incremental work rates. A motion analysis system was used to record their lower limb and lumbar-pelvic kinematics including; bilateral knee joint, bilateral hip joint, lumbar-pelvic joint and pelvic twist angles. These kinematic parameters were analysed at four positions within a normalised rowing stroke. Hip and knee range of motion (ROM) through the stroke were calculated and assessed for asymmetry using the Symmetry Index (Robinson et al., 1987). The step test was performed on an instrumented rowing ergometer which incorporated load cells at the handle and seat so that performance measures such as peak handle force, stroke length, medio-lateral seat drift and stroke power could be derived. Elite rowers exhibited the largest handle force and power (P < 0.01), and least medio-lateral seat drift (P < 0.01). All three groups exhibited lower limb asymmetries, with asymmetries at the hip significantly greater than at the knee (P < 0.01) (Figure 1). Regression analysis indicated that asymmetries in both hip and knee ROM were significant (P < 0.01) in predicting lumbar-pelvic flexion during the power producing phase of the rowing stroke. However, hip ROM asymmetry showed a better relationship with lumbar-pelvic flexion compared to knee ROM asymmetry, explaining a greater proportion of the variance in lumbar-pelvic kinematics. Six rowers exhibited a counterclockwise pelvic twist, however, the direction of pelvic twist did not correspond with the direction of hip joint or knee joint asymmetry. Bilateral asymmetries during the rowing stroke, particularly at the hips, can contribute to sub-optimal kinematics of the lumbar-pelvic region. Quantification of hip ROM asymmetries may therefore be a useful tool in predicting the development of low-back pain in rowers.